Comparison of three single platform methods for CD34+ hematopoietic stem cell enumeration by flow cytometry - Marinov, Iuri; Luxová, Alena; Tkáčová, Vlasta; Gašová, Zdenka; Pohlreich, David; Cetkovský, Petr (Clinical laboratory, 2011)
In the present study, we compared three single platform methods for CD34+ hematopoietic stem cell (HSC) enumeration by flow cytometry. For this purpose, we analyzed the performance characteristics and results obtained from different HSC sources. Interlaboratory coefficients of variation (CV) for precision/reproducibility analysis varied from 4.0% to 6.7% / 6.7% to 9.2% for the low and 3.2% to 4.1% / 4.3% to 6.7%, respectively, for the high stem cell control. Correlation between methods ranged from 0.92% to 0.99%; Wilcoxon test showed no significant differences (p > 0.05); Bland-Altman analysis confirmed good agreement between assays (mean bias ranging from -0.48 to 6.91). Our results demonstrate very good intralaboratory correlation and agreement between methods, confirm the major impact of single platform strategy for accurate and reproducible HSC enumeration and suggest that high interlaboratory variability could be influenced by incorrect performance of validated methods.
Keywords: krevní obraz; krevní buňky; Cell Count; Fluorescent Dyes; daktinomycin; průtoková cytometrie; Bone Marrow Examination; fykoerythrin; fluorescein-5-isothiokyanát; Antigens, CD34; Hematopoietic Stem Cells; Reproducibility of Results; buňky kostní dřeně; antigeny CD34; Antibodies, Monoclonal; lidé; Antineoplastic Agents; Phycoerythrin; protinádorové látky; Flow Cytometry; mobilizace hematopoetických kmenových buněk; Fluorescein-5-isothiocyanate; Dactinomycin; Sensitivity and Specificity; Laboratories; vyšetřování kostní dřeně; Hematopoietic Stem Cell Mobilization; fluorescenční barviva; senzitivita a specificita; laboratoře; faktor stimulující kolonie granulocytů; Granulocyte Colony-Stimulating Factor; reprodukovatelnost výsledků; hematopoetické kmenové buňky; Bone Marrow Cells; počet buněk; Antibody Specificity; Leukapheresis; monoklonální protilátky; specificita protilátek; Blood Cells; leukaferéza; Blood Cell Count; Humans